The Association Between Age at Palatoplasty and Speech and Language Outcomes in Children With Cleft Palate: An Observational Chart Review Study. (February 2020) - Shaffer, Amber D.; Ford, Matthew D.; Losee, Joseph E.; Goldstein, Jesse; Costello, Bernard J.; Grunwaldt, Lorelei J.; Jabbour, Noel
Objective: To determine whether timing of palatoplasty (early, standard, or late) is associated with speech and language outcomes in children with cleft palate. Design: Retrospective case series. Setting: Tertiary care children's hospital. Participants: Records from 733 children born between 2005 and 2015 and treated at the Cleft Craniofacial Clinic of a tertiary children's hospital were retrospectively reviewed. Exclusion criteria were cleft repair at an outside hospital, intact secondary palate, absence of postpalatoplasty speech evaluation, syndromes, staged palatoplasty, and introduction to clinic after 12 months of age. Data from 232 children with cleft palate ± cleft lip were analyzed. Interventions: Palatoplasty. Main Outcome Measures: Speech/language delays and disorders at 20 months and 5 years of age based on formal hospital or community-based testing or screening evaluation in the Cleft Craniofacial Clinic; additional speech surgery. Results: Median age at palatoplasty was 12.6 months (range: 8.8-21.9 months). Age at palatoplasty was classified as early (<11 months, n = 28), standard (11-13 months, n = 158), or late (>13 months, n = 46). Late palatoplasty was associated with increased odds of speech/language delays and speech therapy at 20 months, and language delays at 5 years, compared with standard or early palatoplasty ( P < .05 for all comparisons). However, speech sound production disorders, velopharyngeal incompetence, tube replacement, and hearing loss were not significantly associated with age at palatoplasty. Conclusions: Late palatoplasty may be associated with short- and long-term delays in speech/language development. Future studies with standardized surgical technique/timing and outcome measures are required to more definitively describe the impact of age at palatoplasty on speech/language development.